2021
DOI: 10.1038/s41396-021-00978-y
|View full text |Cite
|
Sign up to set email alerts
|

Deep-sea shipwrecks represent island-like ecosystems for marine microbiomes

Abstract: Biogeography of macro- and micro-organisms in the deep sea is, in part, shaped by naturally occurring heterogeneous habitat features of geological and biological origin such as seeps, vents, seamounts, whale and wood-falls. Artificial features including shipwrecks and energy infrastructure shape the biogeographic patterns of macro-organisms; how they influence microorganisms is unclear. Shipwrecks may function as islands of biodiversity for microbiomes, creating a patchwork of habitats with influence radiating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 32 publications
3
32
0
Order By: Relevance
“…The extent of influence of this shipwreck is comparable with that observed for organic falls (Smith et al 2015). It is possible the shipwreck's influence on the surrounding seabed goes beyond the area examined in this study, based on observations of larger shipwrecks and their microbiomes (Hamdan et al 2021). We note, however, the size and age of sites in the current study are smaller and older, respectively, than previously investigated locations.…”
Section: Shipwreck Core Microbiomes and Differentially Abundant Taxasupporting
confidence: 70%
See 4 more Smart Citations
“…The extent of influence of this shipwreck is comparable with that observed for organic falls (Smith et al 2015). It is possible the shipwreck's influence on the surrounding seabed goes beyond the area examined in this study, based on observations of larger shipwrecks and their microbiomes (Hamdan et al 2021). We note, however, the size and age of sites in the current study are smaller and older, respectively, than previously investigated locations.…”
Section: Shipwreck Core Microbiomes and Differentially Abundant Taxasupporting
confidence: 70%
“…These results are intriguing given that many organic fall studies (Goffredi and Orphan 2010;Fagervold et al 2012) and previous shipwreck studies (Hamdan et al 2018(Hamdan et al , 2021 report increased bacterial diversity with increasing proximity to features. Hamdan et al (2021) reported increased bacterial diversity, and richness surrounding a larger steel-hulled historic shipwreck that extended up to 200 m on the seafloor. In that study, the relationship of proximity and diversity was nonlinear, and instead step-like at intermediate distances.…”
Section: Shipwreck Sedimentary Microbiomes and Geochemistrymentioning
confidence: 74%
See 3 more Smart Citations